Transforming education: exploring the influence of generative AI on teaching performance - Heni Mulyani; Mohamad Azim Istiaq; Elvia R. Shauki; Fitrina Kurniati; Hanifia Arlinda (Cogent Education, 2025)
The emergence of Generative Artificial Intelligence (AI) marks a revolutionary advancement in education. This study explores the profound impact of implementing Generative AI on teachers’ teaching performance, with a focus on enhancing teaching effectiveness and pedagogical practices. This research uses a survey methodology, employing a proportionated stratified random sampling technique. A total of 466 participants, consisting of teachers, were involved in this study, with questionnaires serving as the primary tool for data collection. The primary data analysis method used in this study was the Structural Equation Model (SEM). Research indicates that Generative AI significantly enhances teaching performance by improving ease of use, usefulness, and learning. Teacher perceptions of AI’s usability influence its integration into student-focused learning, learning material development, and teaching practice enhancement. Additionally, the ease of learning is crucial for its adoption. Alongside these promising opportunities, the study also highlights challenges that need to be addressed for successful AI integration in education, such as technical limitations and the necessity for teacher training. By exploring the application of Generative AI in depth, this research offers valuable insights into leveraging technology to foster more inclusive, personalized, and practical education in the digital age.